1985
DOI: 10.3354/meps024177
|View full text |Cite
|
Sign up to set email alerts
|

A deep protozoan maximum in the Gulf of Maine

Abstract: We found a deep maximum In the abundance of larger protozoans (>35 wm) in the Gulf of Maine at depths from 55 to 100 m, which was well below the euphotic zone, pycnocline, and the depths of peak biomass and production of both phytoplankton and b a c t e r~a .Our calculations of the energetics of these protozoan populations suggest that they are unable to obtain sufficient nutrition from local microbial production. We discuss the possibility that organic material, which settles out of the surface layer, might c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…11). This is consistent with observations made in southern California (Beers & Stewart 1970, in the northern Adriatic Sea (Revelante & Gilmartin 1983), and in the Gulf of Maine (Townsend & Cammen 1985), where high concentrations of microzooplankton were found in association with high concentrations of phytoplankton. A correlation coefficient matrix showed significant positive correlations between concentrations of naked oligotrichs and phytoflagellates (Table 4).…”
Section: Factors Affecting Abundance and Distributionsupporting
confidence: 92%
“…11). This is consistent with observations made in southern California (Beers & Stewart 1970, in the northern Adriatic Sea (Revelante & Gilmartin 1983), and in the Gulf of Maine (Townsend & Cammen 1985), where high concentrations of microzooplankton were found in association with high concentrations of phytoplankton. A correlation coefficient matrix showed significant positive correlations between concentrations of naked oligotrichs and phytoflagellates (Table 4).…”
Section: Factors Affecting Abundance and Distributionsupporting
confidence: 92%
“…For example, nanoflagellates in deep waters were more abundant (50-70% higher carbon) than surface assemblage and were dominated by populations of Pnano (Rhodomonas minuta, Cryptomonas species), Pmicro (e.g., Gymnodinium helveticum) and Hmicro (namely Codonella cratera and Tintinnidium fluviatile). Studies from other systems also demonstrate a close association of heterotrophs with phototrophs in DCL (Townsend & Cammen, 1985;Venrick, 1988). A study by Laybourn-Parry & Rogerson (1993) identified a similar subsurface heterotrophic consortium from Lake Windermere, England also similar to that described herein, where they postulated the microheterotrophs merely sank into deep waters along with spring algal blooms that fueled the DCL.…”
Section: Distribution Of Protozoa In Lake Michigansupporting
confidence: 51%
“…1989). Within the COM, the abundance of passive and active suspensionfeeding invertebrates at a depth of 30-45 m coincides with the occurrence of a particulate maximum layer (PML) (Witman and Sebens, 1988;Townsend and Cammen, 1985). and includes a subsurface chlorophyll maximum (Townsend el al., 1984;Morrison and Townsend, 1988).…”
Section: Introductionmentioning
confidence: 98%